Customer Service Information System: Service Improvement Solution PT. Jaringanku Sarana Nusantara - Arditya, I Kadek Dito; Sandhiyasa, I Made Subrata; Supartha, I Kadek Dwi Gandika (PT.KARYA GEMAH RIPAH, 2025)
One of the companies actively involved in the field of information technology systems, especially in the Internet sector is PT Jaringanku Sarana Nusantara. The company has paid services using E-invoice with payment gateway method but on this payment system has not been integrated with microtic devices to perform the disconnection of the Internet for customers who have not paid. This process is carried out through microtic configuration performed by the officers. If the customer's connection termination is missed within the specified limits, the company risks losing the bandwidth cost by continuing to provide internet services without receiving payment on time. In addition to payment services, the company also has a complaint service that uses the WhatsApp app as a medium of interaction with customers, found several problems that need to be addressed. One of the problems was when the admin sent customer data and gave the task division to the team of officers through the WhatsApp group. This research uses the waterfall methodology of a systematic model to develop this system so that it is structured starting from the phases of design, analysis, design, implementation, operation, to the maintenance of the system. The results of this research showed that it was possible to build a service information system at PT. Jaringanku Sarana Nusantara by performing blackbox testing, then it is known that the system is running correctly and in accordance with the expected plan.